Current Situation of Transfusion-Transmitted Malaria in China - Hong Lin (Journal of Tropical Medicine)
Although China is moving toward the eradication of malaria and no indigenous malaria has been reported in most Chinese provinces for several years, recent evaluations have revealed that imported cases remain a major challenge to eliminating malaria, with the number of transfusion-transmitted malaria (TTM) cases increasing over time. Here, we review several TTM case reports published after the implementation of the National Malaria Elimination Program in 2010. A total of 12 TTM cases were reported in China between 2013 and 2018. All recipients and donors were diagnosed using rapid diagnosis test and peripheral blood smears. Plasmodium species in donors with low-density parasites were identified using PCR. Nine (75.0%) were identified as Plasmodium falciparum, two (16.7%) were identified as Plasmodium vivax, and one (8.3%) was identified as Plasmodium ovale. All were imported from malaria-endemic areas. New action plans designed to meet the challenges of TTM are necessary to ensure the elimination of malaria in China. Paying more attention to the frequency of TTM could help to enhance blood safety in China.